Visual function and perinatal focal cerebral infarction. Issue 2 (September 1996) - Mercuri, E; Atkinson, J; Braddick, O; Anker, S; Nokes, L; Cowan, F; Rutherford, M; Pennock, J; Dubowitz, L
Abstract : AIMS: To evaluate the visual function of infants with perinatal cerebral infarction in whom the site and size of the lesion has been determined using magnetic resonance imaging (MRI). METHODS: Twelve infants with cerebral infarction on MRI were studied with a battery of tests specifically designed to evaluate visual function in infancy. This included tests: for visual attention (fixation shifts); of cerebral asymmetry (optokinetic nystagmus, visual fields); for assessment of acuity (forced choice preferential looking); and neurophysiological measures of vision (phase reversal and orientation reversal visual evoked potential). RESULTS: A considerable incidence of abnormalities on at least one of the tests for visual function used was observed. The presence or severity of visual abnormalities could not always be predicted by the site and extent of the lesion seen on imaging. CONCLUSIONS: Early focal lesions affecting the visual pathway can, to some extent, be compensated for by the immature developing brain. These data suggest that all the infants presenting with focal lesions need to be investigated with a detailed assessment of various aspects of vision.